KONFORMITAS HEDONIS DAN LITERASI EKONOMI TERHADAP PERILAKU KONSUMTIF MELALUI GAYA HIDUP KONSUMTIF - Oktafikasari, Eva; Mahmud, Amir (Economic Education Analysis Journal, 2017)
The purpose of this study is to examinate the effect of hedonist conformity and economic literacy on consumtive behavior through consumtive lifestyle. This research is a quantitative research. The research population is bidikmisi student force 2014 at Universitas Negeri Semarang. Sample of this research are 297 students and determined using proportional random sampling. Methods of data collection is using questionnaires, analyzed by descriptive analysis and path analysis. Based on descriptive analysis consumtive behavior, hedonist conformity, economic literacy, and consumtive lifestyle respectively are in the low, low, high, and moderate category. The results showed that (1) hedonist conformity had an effect on consumtive behavior; (2) economic literacy affects consumtive behavior; (3) consumtive lifestyle affects consumtive behavior; (4) hedonist conformity affects consumtive lifesyle; (5) economic literacy has no effect on consumtive lifestyle; (6) consumtive lifestyle mediate hedonist conformity to consumtive behavior; (7) consumtive lifestyle do not mediate economic literacy on consumtive behavior. The conclusion of this research is a role of consumtive lifestyle in mediating hedonist conformity, and has no role in mediating economic literacy on consumtive behavior. The suggestions from this research is that bidikmisi students is not easily affected by their environment.